The Reconstruction of Mental Revolution Concept towards COVID-19 - Darti Busni; Doli Witro; Rahma Fitria Purwaningsih (JSW (Jurnal Sosiologi Walisongo), 2021)
Indonesia is considered unable to handle problems amid the COVID-19 pandemic. The number of work termination (PHK) continues to increase, the debt for countermeasures is also getting bigger, but the pandemic has not been resolved. The concept of the 2014 Mental Revolution should be able to deal with the problems of Indonesian society at critical times. The concept is no longer heard while the public has not lived it. This paper aims to examine the concept of mental revolution during the COVID 19 pandemic. This article uses qualitative research methods, which are literature research. The data in this study were obtained and obtained from the literature. Data reduction, presentation, and conclusion drawing were the data analysis methods used. The analysis results show that the concept of mental revolution in this pandemic situation needs to be echoed again to move dynamically, adjusting the conditions of society during the pandemic period. The concept of mental revolution in community character does not lose the spirit of cooperation in facing both mentally and economically crises. In addition, the policy of shifting to an online system tests the workforce's integrity. However, it has also succeeded in triggering a work ethic and cooperation towards a digital society so that a mental revolution plays a significant role in this situation. Therefore, the Mental Revolution in the series of the Nawacita agenda is expected to run well, continuously, and full of enthusiasm and cooperation in its implementation to survive the pandemic era and achieve national development.